Effects of Two-Phase Mixing Method on Mechanical Properties of Hot Mix Asphalt - Kok, Baha Vurak; Kuloglu, Necati (Lavoisier, 2011)
In this research, in order to improve the mechanical properties of hot mix asphalt, the mixing method was considered. The new method is mainly based on precoating the coarse aggregate with an appropriate amount of optimum binder content. Then the coated coarse aggregate was mixed with fine aggregate + filler and remaining optimum asphalt content. Three types of asphalt cement AC-5. AC-10 and AC-20 was used as binder. To investigate the effectiveness of two-phase mixing method on modified mixtures, the styrene-butadiene-styrene (SBS,Kraton D 1101) modified AC-10 was also used. Basalt was used as aggregate. In conclusion, two-phase mixing method increased the Marshall Quotient, stiffness, creep stiffness, fatigue life and decreased the moisture-induced damage of the hot mix asphalt. It was determined that the efficiency of two-phase mixing system on modified mixtures was greater than that of the unmodified mixtures. A mixing plant for two-phase mixing method was designed to manufacture hot mix asphalt.
Keywords: Mixing method; Precoating; Modified asphalt; Asphalt mixture performance